Factors Causing Burnout: A Systematic Literature Review - Muhammad Derajad; Suhadianto Suhadianto; Igaa Noviekayati (Systematic Literature Review Journal, 2026)
The phenomenon of burnout has evolved into a significant occupational health problem with a prevalence reaching 82% across various global work sectors, especially post-COVID-19 pandemic. This study aims to identify and analyze the causal factors of burnout through a systematic literature review approach using PRISMA 2020 guidelines. Literature search was conducted on four main electronic databases yielding 309 articles which were then selected down to 10 high-quality articles meeting inclusion criteria for the 2021-2025 publication period. Synthesis results indicate that burnout is a multidimensional phenomenon influenced by complex interactions between organizational and individual factors. Dominant organizational factors include work overload, lack of managerial support, unsafe working conditions, and resource inadequacy with burnout prevalence ranging from 17-94%. Individual factors encompass demographic characteristics, coping strategies, resilience, and internal psychological conflicts that serve as moderator variables. Job satisfaction and work meaningfulness function as mediator variables connecting organizational conditions with burnout outcomes. These findings provide theoretical contributions in understanding burnout etiology and can practically serve as a foundation for developing evidence-based preventive interventions to reduce burnout prevalence in work environments.